The Development of an Instrument for Assessing Students' Perceptions of Biology Teachers' Instructional Use of Diagrams - Liu, Yang; Treagust, David; Won, Mihye (Australian Association for Research in Education, 2011)
Science teaching involves using scientific diagrams to explain important concepts, to provide visual images, or to motivate students. However, teachers often wonder if their use of diagrams is effective in helping students learn science. This study aimed to help science teachers evaluate how students perceive their use of diagrams during instruction. Subsequently, we adapted an instrument to measure students' perceptions of science teachers' instructional use of diagrams based on Tuan et al.'s (2000) Student Perceptions of Teachers' Knowledge (SPOTK) questionnaire. The adapted instrument initially had four categories - teacher's instructional practice in using diagrams; teacher's use of multiple forms of scientific representations; teacher's use of diagrams in assessment practices; and students' understanding of and competence in using scientific diagrams. The instrument was administered to 215 Australian high school biology students in Years 9-10. Following factor analysis, 20 items remained in the final instrument and three scales were extracted - Instruction with Diagrams, Assessment with Diagrams, and Students' Diagrammatic Competency. The reliability of the total instrument Students' Perceptions of Teachers' Use of Biology Diagrams was 0.91 and the reliability of each category ranged from 0.65 to 0.90. This instrument is specifically related to the diagrammatic usage in biology lessons and, hopefully, with further research can be generalised to other science lessons. Future research will investigate the relationship between teachers' instruction with diagrams and students' understanding of them.